2014
DOI: 10.3389/fnsys.2014.00186
|View full text |Cite
|
Sign up to set email alerts
|

Representation of pheromones, interspecific signals, and plant odors in higher olfactory centers; mapping physiologically identified antennal-lobe projection neurons in the male heliothine moth

Abstract: The arrangement of anatomically separated systems for information about general and pheromone odorants is well documented at the initial levels of the olfactory pathway both in vertebrates and insects. In the primary olfactory center of the moth brain, for example, a few enlarged glomeruli situated dorsally, at the entrance of the antennal nerve, are devoted to information about female-produced substances whereas a set of more numerous ordinary glomeruli (OG) receives input about general odorants. Heliothine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 44 publications
8
59
0
Order By: Relevance
“…The anti-SYNORF1 (Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, IA, USA) was raised against fusion proteins composed of glutathione-Stransferase and the Drosophila SYN1 protein (SYNORF1; Klagges et al 1996). The specificity of this antibody has been described by Klagges et al (1996), and it is reported to detect synaptic neuropil in various insect species, heliothine moths included (Berg et al 2002;Kvello et al 2009;Zhao et al 2014). After analyzing the mass-stained brains by confocal laser scanning microscopy, the preparation was rehydrated through a decreased ethanol series (10 min each) and rinsed in PBS.…”
Section: Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-SYNORF1 (Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, IA, USA) was raised against fusion proteins composed of glutathione-Stransferase and the Drosophila SYN1 protein (SYNORF1; Klagges et al 1996). The specificity of this antibody has been described by Klagges et al (1996), and it is reported to detect synaptic neuropil in various insect species, heliothine moths included (Berg et al 2002;Kvello et al 2009;Zhao et al 2014). After analyzing the mass-stained brains by confocal laser scanning microscopy, the preparation was rehydrated through a decreased ethanol series (10 min each) and rinsed in PBS.…”
Section: Immunostainingmentioning
confidence: 99%
“…Generally, the findings demonstrate that this tract includes a population of morphologically uniform projection neurons arborizing within one glomerulus. Medial-tract neurons innervating the MGC are reported to target a region both in the calyces and in the lateral horn that is distinct from the region innervated by plant odor neurons (Homberg et al 1988;Kanzaki et al 2003;Zhao et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…social cues, pheromones, and food odors (Hamdani and Døving, 2007). Contrary, in insects, particularly in moths, each of the three main ALTs is formed by axons of projection neurons originating from both the MGC and the ordinary glomeruli (Homberg et al, 1988, Zhao et al, 2014, Kanzaki et al, 2003). Thus, different categories of olfactory cues are processed in all ALTs.…”
Section: Introductionmentioning
confidence: 99%
“…Our results concur that MGC m-mcPNs and l-lcPNs have overlapping projections in ∆LP but we were unable to resolve if uniglomerular m-mcPNs associated with different MGC glomeruli exhibited a separation in their terminal arborizations. However, results from a related heliothine moth, Helicoverpa assulta indicate that such a segregation is likely (Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of PNs in many different moth species have included evaluation of neurophysiological responses to stimulation with odor often partnered with morphological characterization of individual neurons through staining of their antennal lobe dendritic arborizations and terminal target arbors in the protocerebrum (Christensen and Hildebrand, 1987;Kanzaki et al, 1989Kanzaki et al, , 2003Christensen et al, 1991;Hansson et al, 1991;Hansson, 1995, 1997;Lei and Hansson, 1999;Vickers et al, 1998;Lei and Hansson, 1999;Heinbockel et al, 2004;Reisenman et al, 2004;Zhao and Berg, 2010;Zhao et al, 2014). Male moth PNs sensitive to compounds predominantly found in female pheromone blends have dendritic arborizations in the sexually-dimorphic cluster of glomeruli known as the macroglomerular complex (MGC) of the AL (Matsumoto and Hildebrand, 1981;Homberg et al, 1988;Hildebrand 1996).…”
Section: Introductionmentioning
confidence: 99%